A decision support system for the optimal intergration of urban public transport network - Peng, Sheng. (2008)
This study aims to solve a complex public transit optimisation problem analytically with sufficient accuracy under reasonable assumptions. This involves the optimum design of integrated rail and bus networks within an irregular urban area, and the development of a decision support tool based on the obtained models to assist planners in carrying out their planning tasks.